Technological differences between açai and juçara pulps and their sorbets - Ana Paula Silva Siqueira; Kyany Ferreira dos Santos; Thaís Alves Barbosa; Lucas de Alvarenga Santos Freire; Yorran Araújo Camêlo (Brazilian Journal of Food Technology, 2017)
Abstract Açai and juçara are palm trees that produce similar fruits. However, only the sale of açai is growing on the market for pulps and processed products for human consumption. The aim of this study was to compare açai and juçara pulps from the chemical, bioactive, rheological and technological points of view. Sorbets were elaborated with the pulps and evaluations were carried out regarding the antioxidant activity, polyphenols, anthocyanins, pH, acidity, soluble solids, ratio and colour. The pulps were evaluated rheologically and the sorbets for melting time. Juçara showed better results regarding the bioactive parameters (antioxidants ≈ 151 uM ferrous sulphate/ g and anthocyanins ≈ 77 mg.100g-1) and presented a more intense colour (Chroma 17). The pulps were physicochemically similar. The sorbet preserved much of the nutrients and presented a very intense colour, mainly in the juçara sorbet.